Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s10903-009-9234-y
|View full text |Cite
|
Sign up to set email alerts
|

Discussing Depression with Vietnamese American Patients

Abstract: Background Asian patients preferentially seek mental health care from their primary care providers but are unlikely to receive it. Primary care providers need culturally-informed strategies for addressing stigmatizing illnesses. Methods 11 Vietnamese American community members participated in semi-structured interviews. Interviews were audio-taped and transcribed. The grounded theory approach was used for qualitative coding and thematic analysis. Results Vietnamese community members describe experiences with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 12 publications
(13 reference statements)
1
46
0
Order By: Relevance
“…First and foremost, the practice of invoking an RM in this cultural context empowers the patient to behave more assertively in a variety of medical scenarios than they might otherwise do (Fancher et al, 2010; G. T. Nguyen et al, 2007; K. Tran, 2009). One patient manages to circumvent a troublesome administrative requirement (Extract 5), while another invokes an RM in order to obtain a preferred form of treatment (Extract 6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First and foremost, the practice of invoking an RM in this cultural context empowers the patient to behave more assertively in a variety of medical scenarios than they might otherwise do (Fancher et al, 2010; G. T. Nguyen et al, 2007; K. Tran, 2009). One patient manages to circumvent a troublesome administrative requirement (Extract 5), while another invokes an RM in order to obtain a preferred form of treatment (Extract 6).…”
Section: Discussionmentioning
confidence: 99%
“…In studies on the patient's perspective, the main finding has been that these participants tend to adopt an inhibited, compliant attitude towards those who are charged with treating them. Fancher et al (2010) found that the patients in their study rarely expressed their concerns directly unless asked. In G. Nguyen et al (2007), even though most of the patients reported being 1 This author's name consists of a middle name plus first name only (i.e., there is no surname).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…And indeed this expectation is borne out in the extant literature. In studies on the patient's perspective, the salient finding has been that these participants adopt an inhibited, compliant attitude towards those who are charged with treating them (Fancher et al, 2010;Nguyen et al, 2007;Tran, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Culturally-adapted mental health screening instruments have been lacking, and increased research to develop and validate these instruments may better assist providers in making mental health diagnoses. 13 Additionally, replacing stigmatizing terms, [26][27][28] and augmenting the use of interpreters with community advisors, mediators or "culture brokers" may facilitate discussion, diagnosis, and treatment of mental health issues. The findings of this study are limited by the inclusion of patient visits over a 1-year period at a single institution, which limits generalizability.…”
mentioning
confidence: 99%